“Charactery” and books in 2016–2017 - Przybysz-Stawska, Magdalena (Interdyscyplinarium nauk o mediach i kulturze, 2020)
The work discusses the content of the magazine “Charaktery” from the point of view of the information about the book posted there. The collected data was compiled in three groups: as advertisements, reviews, and other information. The quantitative and qualitative content of each group was compared. A thematic profile of the magazine was identified. Preferred lifestyle, personality functions and character traits of the target reader were also described. Characteristic model of the final recipient was made.